STUDI PEMBUATAN ES KRIM BERBASIS SANTAN KELAPA DAN BUBUR UBI JALAR UNGU - Jumiati '; Vonny Setiaries Johan; Yusmarini ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of this study was to determine the effect of coconut milk and purple sweetpotato puree on the quality of the ice cream. This study was conducted experimentally by using completely randomized design (CRD) with five treatments and thre replications. The treatments were K1 (30% coconut milk and 0%purple sweet potato puree), K2 (27.5% coconut milk and 2.5% purple sweet potato puree), K3 (25% coconut milk and 5% purple sweet potato puree), K4 (22.5% coconut milk and 7.5%purple sweet potato puree) and K5 (20% coconut milk and 10% purple sweet potato puree). The obtained data was treated by the analysis of variance by Duncan New Multiple Range Test (DNMRT) at the level of 5%. The best treatment in this research was K3, with fat content of 10.57% and total solids36.78%that has reachedthe quality standardof ice cream (SNI 01-3713-1995), 1.90% protein content, 24.33%overrun, 13.72 minutes for the melting time. Keywords: Ice cream, coconut milk and purple sweet potato